Encapsulation of CO2 into amorphous alpha-cyclodextrin powder at different moisture contents – Part 2: Characterization of complexed powders and determination of crystalline structure. (1st September 2016) - Ho, Thao M.; Howes, Tony; Jack, Kevin S.; Bhandari, Bhesh R.
Highlights: CO2 complex was produced from amorphous α-CD crystallized during complexation. Complex formation was confirmed by appearing of CO2 peak on FTIR and NMR spectra. Crystallization of CO2 complex was illustrated by SEM, NMR, X-ray and DSC. α-CD molecules were arranged in cage-type by which CO2 entrapped in isolated cavity. Abstract: This study aims to characterize CO2 -α-cyclodextrin (α-CD) inclusion complexes produced from amorphous α-CD powder at moisture contents (MC) close to or higher than the critical level of crystallization (e.g. 13, 15 and 17% MC on wet basis, w.b.) at 0.4 and 1.6 MPa pressure for 72 h. The results of 13 C NMR, SEM, DSC and X-ray analyses showed that these MC levels were high enough to induce crystallization of CO2 -α-CD complexed powders during encapsulation, by which amount of CO2 encapsulated by amorphous α-CD powder was significantly increased. The formation of inclusion complexes were well confirmed by results of FTIR and 13 C NMR analyses through an appearance of a peak associated with CO2 on the FTIR (2334 cm −1 ) and NMR (125.3 ppm) spectra. Determination of crystal packing patterns of CO2 -α-CD complexed powders showed that during crystallization, α-CD molecules were arranged in cage-type structure in which CO2 molecules were entrapped in isolated cavities.